Flexible Semiconductor Technologies with Nanoholes-Provided High Areal Coverages and Their Application in Plasmonic-Enhanced Thin Film Photovoltaics. Issue 1 (December 2017) - Wang, Zhaozhao; Peng, Linfa; Lin, Zhongqin; Ni, Jun; Yi, Peiyun; Lai, Xinmin; He, Xiaolong; Lei, Zeyu
Abstract Mechanical flexibility and advanced light management have gained great attentions in designing high performance, flexible thin film photovoltaics for the realization of building-integrated optoelectronic devices and portable energy sources. This study develops a soft thermal nanoimprint process for fabricating nanostructure decorated substrates integrated with amorphous silicon solar cells. Amorphous silicon (a-Si:H) solar cells have been constructed on nanoholes array textured polyimide (PI) substrates. It has been demonstrated that the nanostructures not only are beneficial to the mechanical flexibility improvement but also contribute to sunlight harvesting enhancement. The a-Si:H solar cells constructed on such nanopatterned substrates possess broadband-enhanced light absorption, high quantum efficiency and desirable power conversion efficiency (PCE) and still experience minimal PCE loss even bending around 180°. The PCE performance without antireflection coatings increases to 7.70% and it improves 40% compared with the planar devices. Although the advantages and feasibility of the schemes are demonstrated only in the application of a-Si:H solar cells, the ideas are able to extend to applications of other thin film photovoltaics and semiconductor devices.